TORNAR-SE PROFESSOR DE HISTÓRIA: por que se lê e escreve no curso de História PARFOR/UFRRJ? - Patricia Bastos de Azevedo (Universidade Federal do Maranhão, 2018)
The present article is part of the research in development: Becoming a professor of History: correlations of power and strength in literacy practices in the degree of History PARFOR / UFRRJ. We seek to present the National Plan for the Training of Basic Education Teachers (PARFOR). As focus of analysis, makes use of the portfolio produced by the PARFOR teachers / students in the compulsory discipline of 6th period Teaching of History II. The analysis of the evidence produced seeks to understand what teachers / students write about the experience of reading and writing in the History / PARFOR course, and the implications of these correlations for teacher trainining.